The new public management reforms in Asia: a comparison of south and southeast Asian countries - Samaratunge, Ramanie; Teicher, Julian; Alam, Quamrul (2008)
It has been recognized that there is a need for a cross-country analysis that can be used to identify the factors that contribute to the problems of state incapacity in South and Southeast Asian nations. In taking up this challenge, we explore selected initiatives of new public management (NPM) in the region to analyse cross-country variations. For this purpose we have chosen four South and Southeast Asian countries, namely: Singapore, Malaysia, Sri Lanka and Bangladesh. This article examines how the contextual factors, namely political history, party politics, macroeconomic considerations, state tradition, role of International Development Agencies (IDAs) and the state of civil society, influence the nature and the outcome NPM initiatives in these four countries. We argue that contextual factors played a determining role for which Singapore and Malaysia are relatively successful on their own terms compared to Bangladesh and Sri Lanka, which failed to achieve the expected benefits from NPM reforms. - Reproduced.
Keywords: Public administration; Administrative reform